IMPROVING THE LEARNING OUTCOMES OF 6TH GRADE STUDENTS ON ISLAMIC EDUCATION LESSON THROUGH CANVA-BASED INTERACTIVE VIDEO LEARNING MEDIA AT SDIT HADLONAH DARUSSALAM PONOROGO - Bilqisth, Muhammad Wisnu; Zarkasyi, Azmi (Sindoro: Cendikia Pendidikan, 2025)
This Classroom Action Research addresses the low learning scores of 6th-grade students at SDIT Hadlonah Darussalam, Ponorogo, in Islamic Religious Education. The issues stem from a lack of student engagement and limited teaching methods, primarily lectures, leading to boredom and suboptimal learning. The study aims to (1) enhance student engagement and (2) improve learning outcomes using Canva-based interactive learning media. The research follows two cycles: planning, implementation, observation, and reflection, involving both teachers and observers as researchers. Data was collected through observation sheets, student test results, and documentation. Results show that Canva-based media positively influenced the learning environment. Student activity increased from 46.29% in the first cycle to 87.50% in the second, a 41.21% improvement. Learning outcomes also improved; the percentage of students achieving the minimum competency level (KKM) rose from 26% in the first cycle to 82% in the second. Thus, the study concludes that Canva-based interactive learning media can effectively enhance student engagement and outcomes. The researcher suggests that teachers innovate by integrating flexible and supportive learning media, and future studies should explore different templates, elements, or subjects to further develop Canva's application in education.